Gender Status in the Community School of Nepal (Patan Pragya, 2019)
This paper focused on government and community schools are those schools management responsibility handed over either to the school management committee, or to the local government bodies or to other local organizations for the purpose of improving the quality of education through the active involvement of local communities. School Management Committee (SMC) is the executive body to manage community school. Involvement of local communities in the management of primary and secondary level education is common in South Asia. Much of the enthusiasm of involving communities in the form of decentralisation has come from the assumption that it will empower marginal sections of the society, particularly women to participate in development and governance process of community school development. The study is complemented by both qualitative and quantitative data collected from the selected case study sites and backed by the review of the education policy development processes in different time horizons and also other relevant documents related to the school sector where local communities are being given the responsibilities for managing schools as part of nationwide educational decentralization program. The purpose was to identify factors (both structural and agency related) that constrain or enable women’s participation in community school management.